Ultrathin carrier copper foil and preparation method thereof

By performing pulse plating and copper sulfate plating solution on the carrier copper foil, combined with coarse curing and anti-oxidation treatment, the problem that the existing ultra-thin carrier copper foil cannot meet the high performance requirements is solved, and an ultra-thin carrier copper foil with easy peeling, uniform peeling strength and stability is achieved.

CN119593033APending Publication Date: 2025-03-11ZHEJIANG GARDEN NEW ENERGY CO LTD

Patent Information

Application Number
CN202411735995.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-11

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of copper foils, and particularly relates to an ultrathin carrier copper foil and a preparation method thereof. According to the method, the pulse electroplating alloy electroplating solution with reasonable parameters is adopted on the carrier copper foil, the uniform and compact metal isolation layer is deposited, then the copper sulfate electroplating solution is electroplated, and therefore the ultrathin carrier copper foil which is easy to peel and uniform and stable in peel strength is obtained, and the thickness of the peeled ultrathin copper foil ranges from 2.8 micrometers to 3.2 micrometers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper foil, and in particular to an ultra-thin carrier copper foil and a preparation method thereof. Background Art

[0002] With the rise of big data in recent years, the required supporting hardware has been continuously iterated and updated, bringing with it higher performance requirements for hardware. The demand for the use of packaged integrated and miniaturized components in semiconductor-related products has also increased accordingly.

[0003] Ultra-thin carrier copper foil is one of the key materials used in packaging. However, the ultra-thin carrier copper foil currently required in my country is mainly imported, and Japan's Mitsui carrier copper foil occupies 95% of the global market share. With the rise of national localization, it has become a top priority to develop high-quality, high-performance ultra-thin carrier copper foil as a substitute.

[0004] Application number CN202410331197.0 discloses a method for preparing an ultra-thin carrier copper foil that is easy to peel off, comprising the following steps: step 1, pre-treating the carrier copper foil and immersing it in a high pH stable electrolyte for electrodeposition preparation; step 2, adsorbing the copper foil prepared by electrodeposition with an organic liquid to form an organic layer; step 3, immersing the carrier copper foil forming the organic layer in an electroplating copper solution to prepare the ultra-thin copper foil by electrodeposition. The composite peeling layer of the present invention is obtained by electrochemical deposition and organic adsorption. The composite peeling layer is extremely thin and uniform, and the bonding force between the composite peeling layer and the carrier foil and the ultra-thin copper foil is different, which can make the ultra-thin copper foil after lamination easy to completely and stably peel off from the carrier foil. However, the ultra-thin carrier copper foil still cannot meet the higher requirements now. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides an ultra-thin carrier copper foil and a preparation method thereof, thereby obtaining an ultra-thin carrier copper foil which is easy to peel and has uniform and stable peeling strength.

[0006] In order to achieve the above object, the present invention adopts the following preparation method: Step 1: Use 60-100g / L sulfuric acid as pickling liquid at room temperature to clean the carrier foil, the carrier foil is a refined and polished low-roughness copper foil, and its roughness is 0.5≤Rz≤0.9μm; Step 2: Pulse electroplating alloy plating solution is used on the carrier foil to deposit a multi-element alloy isolation layer; Step 3: Based on step 2, an ultra-thin layer is electroplated using a copper sulfate plating solution to obtain an ultra-thin copper foil layer of 2.8-3.2 μm; Step 4: Based on step 3, the surface of the ultra-thin copper foil is roughly cured to generate copper nodules; Step 5: Post-processing.

[0007] Furthermore, the pulse plating parameters in step 2 are: pulse leading edge time is 20-50us, pulse trailing edge time is 30-100us, pulse frequency is 2-10Hz, duty cycle is 60%, forward current density is 3-12A / dm 2 , reverse current density is 10-30A / dm 2 , the electrodeposition time is 20-40s.

[0008] Furthermore, the alloy plating solution in step 2 comprises three or more of chromium trioxide, pyrophosphate, nickel salt, molybdenum salt, cobalt salt, hypophosphorous acid, boric acid, sulfuric acid, ammonium sulfate, and 4-carboxybenzotriazole, with a total concentration of 20-150 g / L and a plating solution temperature of 35-60°C.

[0009] Furthermore, the alloy plating solution comprises 5 g / L nickel sulfate, 50 g / L cobalt sulfate, 10 g / L boric acid, and 2 g / L 4-carboxybenzotriazole, with a total concentration of 77 g / L, and the plating solution temperature is 50°C.

[0010] Furthermore, the copper sulfate plating solution in step three comprises copper sulfate, ammonium sulfate, sulfuric acid, and hydroxyethyl cellulose, with a total concentration of 100-250 g / L, and a plating solution temperature of 25-50°C.

[0011] Furthermore, the electroplating parameters in step 3 are: current density is 30-50A / dm 2 , the electrodeposition time is 80-100s.

[0012] Furthermore, the post-treatment in step five includes anti-oxidation treatment and silane coupling agent treatment.

[0013] On the other hand, the ultra-thin carrier copper foil prepared according to the above-mentioned method for preparing the ultra-thin carrier copper foil comprises a carrier copper foil layer, a multi-element alloy isolation layer, and an ultra-thin copper foil layer.

[0014] Furthermore, the thickness of the ultra-thin copper foil layer is 2.8-3.2 μm.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention adopts pulse electroplating alloy plating solution with reasonable parameters on the carrier copper foil to precipitate a uniform and dense metal isolation layer, and then electroplates copper sulfate plating solution to obtain an ultra-thin carrier copper foil which is easy to peel and has uniform and stable peeling strength. The thickness of the ultra-thin copper foil after peeling is 2.8-3.2 μm. DETAILED DESCRIPTION

[0016] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto.

[0017] The raw materials used in the embodiments of the present invention are particularly described as follows: 4-Carboxybenzotriazole is CBTA; BT board, full name BT resin substrate material, is a high-performance substrate material used for printed circuit boards.

[0018] Example 1 Step 1: Select 18 μm copper foil with a roughness Rz of 0.9 μm as the carrier foil, and use 80 g / L sulfuric acid as the pickling liquid at room temperature to clean the carrier foil used for support to remove the oxide layer on the surface of the carrier foil.

[0019] The roughness of the carrier copper foil in step one will affect the roughness of the ultra-thin copper foil in step three, and further affect the roughness of the finished product after rough curing in step four. Therefore, it is very necessary to choose a reasonable roughness.

[0020] Step 2: Pulse electroplating alloy plating solution is used on the carrier foil to deposit a multi-element alloy isolation layer; The alloy layer was pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contained 5 g / L nickel sulfate, 50 g / L cobalt sulfate, 10 g / L boric acid, and 2 g / L 4-carboxybenzotriazole, with a total concentration of 77 g / L. The plating solution temperature was 50°C and the pH value was 4.

[0021] The pulse plating parameters are: pulse leading edge time is 20us, pulse trailing edge time is 30us, pulse frequency is 2Hz, duty cycle is 60%, forward current density is 10A / dm 2 , reverse current density is 30A / dm 2 , the electrodeposition time is 30s.

[0022] Step 3: electroplating the ultra-thin layer plating solution on the basis of step 2 to obtain an ultra-thin copper foil of 3 μm; On the basis of step 2, an ultra-thin copper foil layer is electroplated using a plating solution containing 100 g / L copper sulfate, 100 g / L sulfuric acid, and 10 mg / L hydroxyethyl cellulose, with a total concentration of 200.01 g / L and a plating solution temperature of 35°C.

[0023] The electroplating parameters are: current density is 40A / dm 2 The electrodeposition time was 90s, and an ultra-thin copper foil of 3μm was obtained.

[0024] Step 4: Based on step 3, the ultra-thin copper foil is roughly cured to form a copper nodule; On the basis of step 3, a plating solution containing 40 g / L copper sulfate and 100 g / L sulfuric acid was used, the plating temperature was 50°C, and the roughening treatment was performed at a current density of 10 A / dm 2 The electroplating time was 30 s. A plating solution containing 60 g / L copper sulfate and 120 g / L sulfuric acid was used, the plating solution temperature was 25°C, and the curing treatment was performed with a current density of 4 A / dm 2 , the electrodeposition time is 30s.

[0025] Step 5: Post-processing; Anti-oxidation treatment: Based on step 4, a plating solution containing 20 g / L zinc sulfate and 30 g / L boric acid was used at a plating temperature of 50°C for anti-oxidation treatment at a current density of 2 A / dm 2 , the electrodeposition time is 60s.

[0026] Spraying coupling agent treatment: After the anti-oxidation treatment, the surface of the ultra-thin carrier copper foil is sprayed with KBM-403 silane at a concentration of 0.5wt%.

[0027] Example 2 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1. The plating solution contains 5 g / L nickel sulfate, 20 g / L molybdenum sulfate, 100 g / L anhydrous potassium pyrophosphate, and 2 g / L 4-carboxybenzotriazole, with a total concentration of 127 g / L. The plating solution temperature is 50°C and the pH value is 10.

[0028] The pulse plating parameters are: pulse leading edge time is 20us, pulse trailing edge time is 30us, pulse frequency is 10Hz, duty cycle is 60%, forward current density is 10A / dm 2 , reverse current density is 30A / dm 2 , the electrodeposition time is 30s.

[0029] Example 3 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contains 5g / L chromium trioxide, 20g / L sulfuric acid, and 2g / L 4-carboxybenzotriazole, with a total concentration of 27g / L. The plating solution temperature is 50°C and the pH value is 1.5.

[0030] The pulse plating parameters are: pulse leading edge time is 20us, pulse trailing edge time is 30us, pulse frequency is 10Hz, duty cycle is 60%, forward current density is 10A / dm 2 , reverse current density is 30A / dm 2 , the electrodeposition time is 30s.

[0031] Example 4 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contains 5g / L nickel sulfate, 50g / L cobalt sulfate, 10g / L boric acid, and 2g / L 4-carboxybenzotriazole, with a total concentration of 67g / L. The plating solution temperature is 50°C and the pH value is 4.

[0032] The pulse plating parameters are: pulse leading edge time is 50us, pulse trailing edge time is 100us, pulse frequency is 2Hz, duty cycle is 60%, forward current density is 10A / dm 2 , reverse current density is 30A / dm 2 , the electrodeposition time is 30s.

[0033] Example 5 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contains 5g / L nickel sulfate, 50g / L cobalt sulfate, 10g / L boric acid, and 2g / L 4-carboxybenzotriazole, with a total concentration of 67g / L. The plating solution temperature is 50°C and the pH value is 4.

[0034] The pulse plating parameters are: pulse leading edge time is 20us, pulse trailing edge time is 30us, pulse frequency is 2Hz, duty cycle is 60%, forward current density is 10A / dm 2 , reverse current density is 10A / dm 2 , the electrodeposition time is 30s.

[0035] Example 6 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contains 5g / L nickel sulfate, 50g / L cobalt sulfate, 10g / L boric acid, and 2g / L 4-carboxybenzotriazole, with a total concentration of 67g / L. The plating solution temperature is 50°C and the pH value is 4.

[0036] The pulse plating parameters are: pulse leading edge time is 20us, pulse trailing edge time is 30us, pulse frequency is 10Hz, duty cycle is 60%, forward current density is 10A / dm 2 , reverse current density is 30A / dm 2 , the electrodeposition time is 30s.

[0037] Comparative Example 1 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contains 5g / L nickel sulfate, 50g / L cobalt sulfate, 10g / L boric acid, and 2g / L 4-carboxybenzotriazole, with a total concentration of 67g / L. The plating solution temperature is 50°C and the pH value is 4.

[0038] The DC plating method is used, and the current density of the plating is 30A / dm 2 , the electrodeposition time is 10s.

[0039] Comparative Example 2 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contains 5g / L nickel sulfate, 50g / L cobalt sulfate, 10g / L boric acid, and 2g / L 4-carboxybenzotriazole, with a total concentration of 67g / L. The plating solution temperature is 50°C and the pH value is 4.

[0040] The chemical plating method was used and the deposition time was 300 s.

[0041] Comparative Example 3 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer was pulse electroplated on the smooth surface of the carrier foil treated in step 1, and the plating solution contained 50 g / L nickel sulfate, 130 g / L cobalt sulfate, 10 g / L boric acid, and 2 g / L 4-carboxybenzotriazole, with a total concentration of 192 g / L. The plating solution temperature was 30°C.

[0042] The current density of pulse plating is 30A / dm 2 , the electrodeposition time is 10s.

[0043] Comparative Example 4 The preparation process is basically the same as that in Example 1, except that in step 2: The alloy layer is pulse electroplated on the smooth surface of the carrier foil treated in step 1. The plating solution contains 5 g / L nickel sulfate, 50 g / L cobalt sulfate, 10 g / L boric acid, and 2 g / L 4-carboxybenzotriazole, with a total concentration of 67 g / L. The plating solution temperature is 20°C and the pH value is 4.

[0044] The current density of pulse plating is 30A / dm 2 , the electrodeposition time is 10s.

[0045] Performance Testing In order to more clearly show the effect of the preparation formula and pulse plating process of different embodiments on the quality of ultra-thin copper foil, the carrier copper foils prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to peeling force tests. The carrier copper foil samples were laminated on the BT substrate at a pressure of 25 MPa and a lamination temperature of 220°C for 90 minutes, and the laminated samples were cut into strips of 12.7 mm × 150 mm, and a universal material stripping machine was used for the peeling experiment. The thickness of the isolation layer after deposition was measured using a transmission electron microscope. The test results are shown in Table 1 below.

[0046] Table 1 Performance Test Results It can be seen from Examples 1-6 that the film can be peeled off both before and after lamination, and the peeling force is uniform, the thickness of the isolation layer is appropriate, and the peeling force after lamination is moderate, and an ultra-thin carrier copper foil that is easy to peel and has uniform and stable peeling strength is obtained.

[0047] It can be seen from Example 1 and Comparative Examples 1-2 that the peeling force uniformity of Comparative Example 1 is uneven, Comparative Example 2 is difficult to peel off after pressing and its isolation layer thickness is relatively small, and the result obtained by the pulse plating method in step 2 is better than the two deposition methods of DC plating and chemical plating.

[0048] It can be seen from Examples 1-6 and Comparative Examples 3-4 that the comparative example 3 is partially peeled off after pressing and the peeling force is uneven, the thickness of the isolation layer of the comparative example 4 is too small, and the alloy plating solution formula in step 2 of the embodiment is better.

[0049] The specific embodiments described herein are merely examples of the invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the invention or exceed the scope defined by the appended claims.

Claims

1. A method for preparing an ultra-thin carrier copper foil, characterized in that: Step 1: Use 60-100g / L sulfuric acid as pickling liquid at room temperature to clean the carrier foil, the carrier foil is a refined and polished low-roughness copper foil, and its roughness is 0.5≤Rz≤0.9μm; Step 2: Pulse electroplating alloy plating solution is used on the carrier foil to deposit a multi-element alloy isolation layer; Step 3: Based on step 2, an ultra-thin layer is electroplated using a copper sulfate plating solution to obtain an ultra-thin copper foil layer of 2.8-3.2 μm; Step 4: Based on step 3, the surface of the ultra-thin copper foil is roughly cured to generate copper nodules; Step 5: Post-processing.

2. The method for preparing an ultra-thin carrier copper foil according to claim 1, characterized in that: The pulse plating parameters in step 2 are: pulse front time 20-50us, pulse back time 30-100us, pulse frequency 2-10Hz, duty cycle 60%, forward current density 3-12A / dm 2 , reverse current density is 10-30A / dm 2 , the electrodeposition time is 20-40s.

3. The method for preparing an ultra-thin carrier copper foil according to claim 1, characterized in that: The alloy plating solution in step 2 comprises three or more of chromium trioxide, pyrophosphate, nickel salt, molybdenum salt, cobalt salt, hypophosphorous acid, boric acid, sulfuric acid, ammonium sulfate, and 4-carboxybenzotriazole, with a total concentration of 20-150 g / L and a plating solution temperature of 35-60°C.

4. The method for preparing an ultra-thin carrier copper foil according to claim 3, characterized in that: The alloy plating solution comprises 5 g / L nickel sulfate, 50 g / L cobalt sulfate, 10 g / L boric acid, and 2 g / L 4-carboxybenzotriazole, with a total concentration of 77 g / L, and the plating solution temperature is 50°C.

5. The method for preparing an ultra-thin carrier copper foil according to claim 1, characterized in that: The copper sulfate plating solution in step 3 comprises copper sulfate, ammonium sulfate, sulfuric acid and hydroxyethyl cellulose, with a total concentration of 100-250 g / L and a plating solution temperature of 25-50° C.

6. The method for preparing an ultra-thin carrier copper foil according to claim 1, characterized in that: The electroplating parameters in step 3 are: current density is 30-50A / dm 2 , the electrodeposition time is 80-100s.

7. The method for preparing an ultra-thin carrier copper foil according to claim 1, characterized in that: The post-treatment in step five includes anti-oxidation treatment and silane coupling agent treatment.

8. An ultra-thin carrier copper foil, characterized in that: It is prepared according to the method for preparing the ultra-thin carrier copper foil according to any one of claims 1 to 7.

9. The ultra-thin carrier copper foil according to claim 8, characterized in that: The ultra-thin carrier copper foil comprises a carrier copper foil layer, a multi-element alloy isolation layer and an ultra-thin copper foil layer.

10. The ultra-thin carrier copper foil according to claim 9, characterized in that: The thickness of the ultra-thin copper foil layer is 2.8-3.2 μm.

Citation Information

Patent Citations

  • Preparation method of easy-to-peel ultrathin carrier copper foil

    CN118223084A

Cited By

  • A titanium electrode surface modifier for electrodeposition of copper foil and a preparation method thereof

    CN122791442A